Endoscopic third ventriculostomy - Ammar M. Al-Smaysim; Waleed K. Alhayali; Salima B. Alsaadi; Aanab O. Abdulameer; Mustafa Ismail; Samer S. Hoz (Romanian Neurosurgery, 2022)
Introduction. Endoscopic third ventriculostomy (ETV) is the treatment of choice in obstructive hydrocephalus. It has become the main standard choice in management since 1962. However, there is scant data regarding the complications from clinical or multi-centre trials. This study highlights the specific complications and prevention methods related to ETV in Neurosurgical Teaching Hospital, Baghdad, Iraq.